2008
DOI: 10.3928/1081597x-20080601-07
|View full text |Cite
|
Sign up to set email alerts
|

PRK and Butterfly LASEK: Prospective, Randomized, Contralateral Eye Comparison of Epithelial Healing and Ocular Discomfort

Abstract: PURPOSE: To compare corneal reepithelialization, pain scores, ocular discomfort, and tear production after photorefractive keratectomy (PRK) and butterfl y laser epithelial keratomileusis (LASEK). METHODS: This prospective, randomized, doublemasked study comprised 102 eyes of 51 patients who underwent laser refractive surgery. Each patient was randomized to have one eye operated on with PRK and the other with butterfl y LASEK. Patients were followed for 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 26 publications
0
36
0
2
Order By: Relevance
“…89,90 Epithelial healing ranges from 3.2 to 4.35 days for PRK and 3.6 to 4.8 days for LASEK. 18,91,92 In the study by Lee et al, 18 pain scores were significantly higher in the PRK group, with an mean score of 2.3 out of 4.0 for PRK compared with 1.6 for LASEK. Pirouzian et al 93 report no difference in pain scores and show that on day 1, LASEK patients had smaller epithelial defects, but by day 3, PRK eyes had smaller epithelial defects.…”
Section: Comparative Surface Ablation Studiesmentioning
confidence: 93%
See 2 more Smart Citations
“…89,90 Epithelial healing ranges from 3.2 to 4.35 days for PRK and 3.6 to 4.8 days for LASEK. 18,91,92 In the study by Lee et al, 18 pain scores were significantly higher in the PRK group, with an mean score of 2.3 out of 4.0 for PRK compared with 1.6 for LASEK. Pirouzian et al 93 report no difference in pain scores and show that on day 1, LASEK patients had smaller epithelial defects, but by day 3, PRK eyes had smaller epithelial defects.…”
Section: Comparative Surface Ablation Studiesmentioning
confidence: 93%
“…Lee et al 18 report that haze scores at 1 month were significantly greater in the PRK group. However, Ghanem et al 92 report a slight increase in haze formation in patients receiving LASEK over PRK.…”
Section: Comparative Surface Ablation Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Although most comparative studies of PRK and LA-SEK report a higher haze incidence in PRK, Litwak et al 51 and Hashemi et al, 52 in accordance with our findings, observed no significant difference. Over a 12-month period, Ghanem et al 53,54 observed significantly more haze 1 month after butterfly LASEK than after PRK; however, there were no significant differences in haze thereafter. Furthermore, Hashemi et al found a greater tendency toward haze formation with LASEK.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, the decision to reposition or to remove the epithelial flap seems a crucial difference, and some studies comparing the 2 methods have been performed. 35,38,[48][49][50] Prospective clinical studies comparing techniques are shown in Table 3 30,[38][39][40]44,46,47,[51][52][53][54][55][56][57] and laboratory studies in Table 4. 32,58,59 However, these studies yielded partly contradictory conclusions.…”
Section: Discussionmentioning
confidence: 99%